At home in Shenzhen? Housing opportunities and housing preferences of creative workers in a wannabe creative city. Issue 2 (2nd July 2016) - Bontje, Marco
Abstract : Shenzhen grew fast as a city of industrial mass-production, but is transforming to an innovative and creative city. Shenzhen's policies to encourage the creative industries are mostly aimed at companies and entrepreneurs. To really become an attractive creative city, housing policies for creative talent should be added. This article reports on an interview-based analysis of the housing situation and residential preferences of creative workers in Shenzhen. While creatives with good salaries have no problems finding attractive homes and neighbourhoods in Shenzhen, there is a shortage of affordable neighbourhoods meeting the demands of recent graduates and starting creatives. Shenzhen's creative city strategy should take the socio-economic diversity of creative workers into account.